2009
DOI: 10.1186/1475-925x-8-6
|View full text |Cite
|
Sign up to set email alerts
|

Research and development of a new RF-assisted device for bloodless rapid transection of the liver: Computational modeling and in vivo experiments

Abstract: Background: Efficient and safe transection of biological tissue in liver surgery is strongly dependent on the ability to address both parenchymal division and hemostasis simultaneously. In addition to the conventional clamp crushing or finger fracture methods other techniques based on radiofrequency (RF) currents have been extensively employed to reduce intraoperative blood loss. In this paper we present our broad research plan for a new RF-assisted device for bloodless, rapid resection of the liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 30 publications
1
13
0
3
Order By: Relevance
“…The effect of free convection at the tissue-ambient and device-ambient interfaces was taken into account using a thermal 245 transfer coefficient (h e ) of 20 W m −2 K −1 and a value of 21ºC was considered for ambient temperature. 25 The cooling effect produced by the fluid circulating inside the device was not modeled realistically by means of internal tubes (the device was empty, …”
Section: Iic Computer Modelingmentioning
confidence: 99%
“…The effect of free convection at the tissue-ambient and device-ambient interfaces was taken into account using a thermal 245 transfer coefficient (h e ) of 20 W m −2 K −1 and a value of 21ºC was considered for ambient temperature. 25 The cooling effect produced by the fluid circulating inside the device was not modeled realistically by means of internal tubes (the device was empty, …”
Section: Iic Computer Modelingmentioning
confidence: 99%
“…Experiments were conducted in these studies to determine convective heat transfer coefficients in the heart as well as the heart tissue properties [8][9][10]. Much of the subsequent research drew heavily on this initial work for geometry, tissue properties and convection coefficients for blood flow in the heart, notably Berjano and co-workers [4,[11][12][13][14]. A proven computational model strategy has emerged from the research and several aspects of that model will be considered in detail here.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, to our knowledge, no previous references have demonstrated any definitive effect on LHER. Previous studies of our group have shown that RF-assisted liver transection could achieve a wide ablation margin (up to 1 cm) without increasing the risk of thermal damage in nearby structures [22,[27][28][29][30]. In this setting, the aim of this study was to determinate whether RF-assisted liver transection reduces local hepatic recurrence over the standard methods especially when this margin was positive.…”
Section: Introductionmentioning
confidence: 97%